Process-Oriented Guided Inquiry Learning (POGIL) as a Culturally Relevant Pedagogy (CRP) in Qatar: a Perspective from Grade 10 Chemistry Classes - Treagust, David; Qureshi, S.; Vishnumolakala, Venkat Rao; Ojeil, J.; Mocerino, Mauro; Southam, Daniel (Springer, 2018)
© 2018 Springer Science+Business Media B.V., part of Springer Nature Educational reforms in Qatar have seen the implementation of inquiry-based learning and other student-centred pedagogies. However, there have been few efforts to investigate how these adopted western pedagogies are aligned with the high context culture of Qatar. The study presented in this article highlights the implementation of a student-centred intervention called Process-Oriented Guided Inquiry Learning (POGIL) in selected independent Arabic government schools in Qatar. The study followed a theoretical framework composed of culturally relevant pedagogical practice and social constructivism in teaching and learning. A mixed method research design involving experimental and comparison groups was utilised. Carefully structured learning materials when implemented systematically in a POGIL intervention helped Grade 10 science students improve their perceptions of chemistry learning measured from pre- and post-tests as measured by the What Is Happening In this Class (WIHIC) questionnaire and school-administered achievement test. The study further provided school-based mentoring and professional development opportunities for teachers in the region. Significantly, POGIL was found to be adaptable in the Arabic context.